2015
DOI: 10.1002/chem.201502926
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics with Explicit Solvent Reveals a Two‐Step Pathway in the Frustrated Lewis Pair Reaction

Abstract: The role solvent plays in reactions involving frustrated Lewis pairs (FLPs)-for example, the stoichiometric mixture of a bulky Lewis acid and a bulky Lewis base-still remains largely unexplored at the molecular level. For a reaction of the phosphorus/boron FLP and dissolved CO2 gas, first principles (Born-Oppenheimer) molecular dynamics with explicit solvent reveals a hitherto unknown two-step reaction pathway-one that complements the concerted (one-step) mechanism known from the minimum-energy-path calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Our previous studies concerning A•••B complexes with B being CO2 are reported in references [36][37][38][39][40][41]. Simulation of phosphorous/boron frustrated lewis pair complexes (FLP) with CO2 in explicit solvent proposed a two-step mechanism [42]. The effect of the solvent has been considered on the carbene + CO2 reaction [43,44] and in the anion + CO2 one [45].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies concerning A•••B complexes with B being CO2 are reported in references [36][37][38][39][40][41]. Simulation of phosphorous/boron frustrated lewis pair complexes (FLP) with CO2 in explicit solvent proposed a two-step mechanism [42]. The effect of the solvent has been considered on the carbene + CO2 reaction [43,44] and in the anion + CO2 one [45].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note the still approximate nature of such simulations: the approximations used may result in artifacts, such as over‐structured water . At the moment, a few small molecules surrounded by less that 100 water molecules can be simulated by these methods on ∼ 10 ps time‐scale, enough to investigate a chemical reaction pathway . These time‐scales are not comparable to what is now possible with classical water models: 10 μs is becoming routine, and the cutting edge simulations begin to reach into milliseconds.…”
Section: Explicit Water Modelsmentioning
confidence: 99%
“…fixed charge force fields, polarisable force fields and hybrid quantum mechanics/molecular mechanics (QM/MM) potentials. [15][16][17] There has been some success in the application of explicit solvent models to predict organic and inorganic reaction mechanisms, [18][19][20] electrochemistry, [21][22][23][24][25][26][27] and pKa values. [28][29][30][31] However, given the size of these systems and the need for extensive configurational sampling, explicit solvent simulations are generally carried out using classical MM force fields or hybrid QM/MM potentials.…”
Section: Introductionmentioning
confidence: 99%